The Everyday Life of Memorials - Shanken, Andrew M. (Book collections on Project MUSE., 2022)
"This book works with the literature of the everyday, memory studies, and non-representational geography to open up a novel understanding of memorials not just as everyday objects, but also as fundamental to urban modernity"--